ESTETIKA MUSIK TALEMPONG LAGU DENDANG DI NAGARI LIMBANANG - Nadya Fulzi (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2011)
Talempong pacik is a traditional ensemble that can be found all over Minangkabau region. It has a variety of instrumentation and song repertoire, but the musical concept is the same; it uses interlocking technique to build the melody. The basic principle in talempong pacik ensemble is playing melodious motifs by three talempong players by emphasizing the improvization aspect. There is an impression that the sounds of talempong are arguing aginst each other, an analogy to the concept of dialectic, that is, the skill to converse and argue based on the right argument and logic. Dialectic itselt is part of Minangkabau culture. So the concept of dialectic is a basic musical concept dan philosophy of talempong pacik